Post-stroke depression: diagnostic difficulties and treatment perspectives - S. Iu. Maltcev; V. A. Mikhailov; G. E. Mazo; L. V. Lukina (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
A plenty of studies show that the post- stroke depression is a difficult and complex problem, which bids defiance to the whole rehabilitation system. The solution of this objective definitely needs some specific diagnostic utilities and the most actual treatment methods. At the same time, there are some reasons, which do not allow us to reach an optimal rehabilitation result. In our paper we are reviewing both diagnostic problems of a post- stroke depression and some of the most promising diagnostic and treatment techniques, and hope that will help us solving an issue.